THE PRODUCTION OF PUBLIC SPACE ON RUSSIAN TV POLITICAL TALK-SHOW / ПРОИЗВОДСТВО ПУБЛИЧНОГО ПРОСТРАНСТВА НА РОССИЙСКОМ ТВ: ПОЛИТИЧЕСКИЕ ТОК-ШОУ - YAKOVLEVA A.M. / ЯКОВЛЕВА А.М. (Наука телевидения, 2017)
How seemingly natural public space generated by the TV, is really natural? The author states that the real public space is almost entirely supplanted by a virtual public space – in particular, television: with extras instead of society and professional speakers. It seems that these are the «new frontiers», which, having replaced the old ones, replaced the model of public space with quasimodel, being translated now by Russian TV channels of the extremely involving media.